(3GdeGA GdhQbj hGdCQV GdfLejIs - (3GdJejej, CHh YHO Gddg, eMeO Hf Cejd Hf YHO Gddg Hf Cejd, J (B170 (3g`s ((3eMeO Hf Ydj GdSQGL (B( (3beTGf (B)s)
(3ChdgG (B:s
(3HSe Gddg bGd eMeO Hf Gejd ONdJ CfG hCHh GdbGSe hYHO GdQMef CNh CHh GdaVd LYaQ GdfMhj hef HYO Pdc aVdJ CfG hCHh GdMSf Ydj Hf CMeO Hf YHO GdhGMO GdeYQha HGdYOhj s
(3BNQgG (B:s
(3hCcKQ Pdc Ydi GdeLGR hHYVg Ydi GdMbjbI aj HYV GdJTHjg EfeG WdHJ GdMceGA HgPG GdJTHjg cdg GdhMj ef cdGege hGdEjeGf GdPj jDefhf Hg Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\ 139s
(3cTa GdXfhf (B2\1576s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs